Experimental Assessment of Green Waste HTC Pellets: Kinetics, Efficiency and Emissions - Yaniel Garcia Lovella; Abhishek Goel; Louis Garin; Julien Blondeau; Svend Bram (Energies)
The combustion of renewable solid fuels, such as biomass, is a reliable option for heat and power production. The availability of biomass resources within urban areas, such as tree leaves, small branches, grass, and other green city waste, creates an opportunity to valorize such resources. The energy densification of such resources using hydrothermal carbonization (HTC) and pelletization of the carbonized material could create a new generation of domestic boiler biofuel. However, combustion efficiency and emission assessments should be carried out for HTC pellets. The primary objective of this study is to assess HTC pellets, provided by a waste upgrade company, in terms of kinetics, combustion efficiency, and emissions, taking as reference base ENplus A1 certified softwood pellets. Therefore, thermogravimetric analysis and combustion tests were conducted for both fuels to achieve this. It was observed that a third peak of the burning rate during the solid carbon oxidation of HTC pellets indicated a high activation energy. Combustion tests showed a 7% increase in boiler efficiency for HTC pellets compared to softwood pellets. However, higher particulate matter (PM), NOx, and CO emissions were recorded during the HTC pellets test. The results suggest that optimizing the air/fuel ratio could further improve the performance of HTC pellets in domestic boilers.